2020
DOI: 10.3390/plants9030297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant on Glyphosate Effectiveness, Retention, Absorption and Translocation in Lolium rigidum and Conyza canadensis

Abstract: Glyphosate retention, absorption and translocation with and without adjuvant were examined in Lolium rigidum and Conyza canadensis in greenhouse and laboratory settings to develop an understanding of the influence of the selected adjuvant on glyphosate activity. Tests on whole plants show that the dose of herbicide needed to reduce dry weight by 50% (GR50) or plant survival (LD50) decreases by mixing glyphosate and adjuvant to 22%–24% and 42%–44% for both populations of L. rigidum and C. canadensis, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
(46 reference statements)
0
30
0
1
Order By: Relevance
“…The results found in the present study indicate that the addition of an adjuvant can significantly reduce GR 50 values in resistant C. sumatrensis, irrespective of the glyphosate formulation. This advantage of adjuvant use demonstrates that costs of herbicide treatments can be significantly reduced, avoiding the increase in herbicide rates for the control of weeds such as those belonging to the genus Conyza [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results found in the present study indicate that the addition of an adjuvant can significantly reduce GR 50 values in resistant C. sumatrensis, irrespective of the glyphosate formulation. This advantage of adjuvant use demonstrates that costs of herbicide treatments can be significantly reduced, avoiding the increase in herbicide rates for the control of weeds such as those belonging to the genus Conyza [7].…”
Section: Discussionmentioning
confidence: 99%
“…This mode of action leads to lethal injuries to susceptible plants [2]. Thus, this herbicide has been successfully and extensively used in a broad range of agricultural and non-agricultural areas both against monocot and dicot weeds [7]. Glyphosate in its various formulations has been continuously applied, especially in recent 2 of 12 decades, in orchards, vineyards, olive groves and cereal fields in many countries of the Mediterranean basin [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the lower the LD 50 , the more toxic the pesticide (Raj et al, 2013). A recent study has shown that mixing nonionic adjuvants with glyphosate influenced the LD 50 of glyphosate in horseweed ( Conyza canadensis ) and ryegrass ( Lolium rigidum ), and increased the effectiveness of glyphosate (Palma‐Bautista et al, 2020). Surfactants that help to improve accumulation of pesticides may increase the human health risk posed by those pesticides.…”
Section: General Consideration For Surfactants In Plant Disease Managmentioning
confidence: 99%
“…To improve efficacy of pesticides, novel tools to deliver the chemicals efficiently to target sites in plants, pathogens, and pathogen vectors are concurrently developed. Such novel tools include nano‐based formulations, improved spraying technology, and improvements in surfactants, among others (Huang et al, 2018; Palma‐Bautista et al, 2020; van Zyl et al, 2010, 2014). Surfactants have traditionally played substantial roles in crop protection, especially in the 20th century, and their use has increasingly become important in 21st century agriculture (Castro et al, 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used for the foliar retention was described by Palma-Bautista et al (2020) with some modifications and carried out at the University of Córdoba (Spain). Young plants with 4–6 leaves of R and S B. catharticus populations were sprayed with 360 g ae ha −1 of glyphosate and 100 mg L −1 Na-fluorescein using a laboratory system (SBS-060 De Vries Manufacturing, Hollandale, MN, United States) equipped with 8002 flat fan nozzles delivering 200 L ha −1 at 250 kPa at the height of 50 cm from plant level.…”
Section: Methodsmentioning
confidence: 99%